2021
DOI: 10.1039/d1ra03563k
|View full text |Cite
|
Sign up to set email alerts
|

Phthalimide conjugation turns the AIE-active tetraphenylethylene unit non-emissive: its use in turn-on sensing of hydrazine in solution and the solid- and vapour-phase

Abstract: A new AIE-based fluorimetric probe (TPE-PMI) has been successfully developed utilizing Gabriel reaction for the selective detection of hydrazine in solid, liquid and vapour phases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Since the invention of aggregation-induced emission-active silole molecules by Tang’s group in 2001, this field has been the focus of extensive research in the last two decades . However, there are only limited attempts of to make AIEgens using mechanochemistry. , …”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
See 2 more Smart Citations
“…Since the invention of aggregation-induced emission-active silole molecules by Tang’s group in 2001, this field has been the focus of extensive research in the last two decades . However, there are only limited attempts of to make AIEgens using mechanochemistry. , …”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
“…51 However, there are only limited attempts of to make AIEgens using mechanochemistry. 52,53 Very recently, Hiremath et al reported the mechanochemical synthesis of a tetraphenylethylene (TPE)-based probe for the selective detection of hydrazine (Figure 6). 52 In a solvent-free approach, TPE-NH 2 (54) was condensed with phthalic anhydride in a mixer mill (MM400) in SS jar for 1 h at 30 Hz followed by heating in a sand bath for 2 h at 230 °C to afford the probe (55) in excellent yield (94%).…”
Section: Mechanochemical Synthesis and Modification Of Fluorophores F...mentioning
confidence: 99%
See 1 more Smart Citation
“…40 Currently, the development of fluorescent probes with high sensitivity, high selectivity, and low toxicity for N 2 H 4 recognition remains challenging. 41–44…”
Section: Introductionmentioning
confidence: 99%
“…12 Such oxidative stress can lead to a variety of diseases involving DNA mutations, aberrant electron transport, disruption of calcium homeostasis, activation of apoptosis, cardiovascular diseases, neuron degeneration, arthritis, and cancer. 13 Several studies have been reported so far by researchers based on the adverse impact of both hydrazine and hypochlorite towards flora and fauna, [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] albeit there is significant room for improvement.…”
Section: Introductionmentioning
confidence: 99%